2016
DOI: 10.1007/s00132-016-3317-y
|View full text |Cite
|
Sign up to set email alerts
|

Bizarre paraosseale osteochondromatöse Proliferation der Metatarsalknochen

Abstract: A bizarre parosteal osteochondromatous proliferation (BPOP), also known as a Nora lesion, is a rare benign bone formation. It emanates mainly from the intact cortex of the metaphysis of short tubular bones (hands or feet). Conventional radiographs should be complemented using cross-sectional imaging modalities (CT/MRI). In the absence of symptoms a non-operative regime with radiological and clinical controls is possible. If symptomatic, excision biopsy is the treatment of choice, though a high recurrence rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Several studies have reported various surgical excision approaches. 3 , 5-7 , 9 , [13][14][15][16][17] First, simple excision (marginal excision) is widely known. 3 , 6 , 12 It is indicated for symptomatic BPOP cases and remains the preferred treatment for primary lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported various surgical excision approaches. 3 , 5-7 , 9 , [13][14][15][16][17] First, simple excision (marginal excision) is widely known. 3 , 6 , 12 It is indicated for symptomatic BPOP cases and remains the preferred treatment for primary lesions.…”
Section: Discussionmentioning
confidence: 99%
“…1 Other exams, such as Computed Tomography (CT-Scan) or Magnetic Resonance (MRI), can give more detailed information in order to plan a correct therapeutic approach. 10 On MRI, Nora's lesion presents with bone cortex involvement without medullary involvement, periosteal reaction or soft tissue swelling. 11 However, the definitive diagnosis is given by the histopathological examination.…”
Section: Discussionmentioning
confidence: 99%